2016
DOI: 10.1038/srep25193
|View full text |Cite
|
Sign up to set email alerts
|

Ecological restoration alters microbial communities in mine tailings profiles

Abstract: Ecological restoration of mine tailings have impact on soil physiochemical properties and microbial communities. The surface soil has been a primary concern in the past decades, however it remains poorly understood about the adaptive response of microbial communities along the profile during ecological restoration of the tailings. In this study, microbial communities along a 60-cm profile were investigated in a mine tailing pond during ecological restoration of the bare waste tailings (BW) with two vegetated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
33
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 59 publications
8
33
1
1
Order By: Relevance
“…In the revegetation area, plant litter and root exudate contributed a large amount of organic nitrogen (Baxendale et al, 2014;Thion et al, 2016), and the inorganic nitrogen mineralized by this organic nitrogen was provided to plants and microbes (Thion et al, 2016). In the area revegetated by C. zizanioides, the phytocommunity obtained the inorganic nitrogen in the process of nitrogen transformation and grew well, but the TN in the tailings experienced no improvement compared to the bare wastelands assayed in our previous study (Li et al, 2016a). In contrast, plant-derived C from I. cylindrica stimulated the activity of nitrogen fixing bacteria.…”
Section: Discussionmentioning
confidence: 96%
“…In the revegetation area, plant litter and root exudate contributed a large amount of organic nitrogen (Baxendale et al, 2014;Thion et al, 2016), and the inorganic nitrogen mineralized by this organic nitrogen was provided to plants and microbes (Thion et al, 2016). In the area revegetated by C. zizanioides, the phytocommunity obtained the inorganic nitrogen in the process of nitrogen transformation and grew well, but the TN in the tailings experienced no improvement compared to the bare wastelands assayed in our previous study (Li et al, 2016a). In contrast, plant-derived C from I. cylindrica stimulated the activity of nitrogen fixing bacteria.…”
Section: Discussionmentioning
confidence: 96%
“…A similar result was also reported by Li et al [9] who found that the addition of native soil to Cu-Pb-Zn tailings significantly changed the composition and structure of microbial communities. Therefore, incorporation of amendments may fast-track the establishment of microbial community and initiate the rehabilitation of biogeochemical process of mine soils [2,9].…”
Section: Discussionmentioning
confidence: 99%
“…Mining can transform fertile, cultivated land into unfertile land. One way is by altering the structural and function of the soil microbial community [1,2]. Remediation of mine wastelands is one of the pressing needs to be addressed for social and economic development to be healthy and sustainable.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that the soil microbial community changed markedly after ecological restoration (Li et al, 2016;Yan et al, 2018). The results from Li et al (2016) have shown that significant differences existed in the relative abundance of bacteria in some phyla after restoration. Yan et al (2018) observed that a dramatic shift in the fungal community toward that of the natural fungal community occurred after only 10 years of active native plant revegetation.…”
Section: Introductionmentioning
confidence: 99%
“…Microorganisms (bacteria and fungi) may serve as possible bio-indicators for monitoring soil ecosystem functions in close association with changes in the physicochemical and biological conditions during the ecological restoration of degraded areas (Mendez, García, Maestre, & Escudero, 2008;Wang et al, 2012). Previous studies showed that the soil microbial community changed markedly after ecological restoration (Li et al, 2016;Yan et al, 2018). The results from Li et al (2016) have shown that significant differences existed in the relative abundance of bacteria in some phyla after restoration.…”
Section: Introductionmentioning
confidence: 99%